Analisis Penerapan Aspek Perpajakan Koperasi Balai Diklat Keagamaan Padang - Yunita Valentina Kusufiyah; Dwi Zahara Junaidi; Reni Dahar (Universitas Dharma Andalas, 2026)
Tax is the main source of state revenue that plays an important role in supporting national development financing and improving public welfare. In order to enhance taxpayer compliance, the government has implemented the modernization of tax administration systems through e-registration, e-SPT, e-form, e-filing, and e-billing. This study aims to analyze the implementation of taxation aspects at the Balai Diklat Keagamaan Cooperative in Padang as a form of taxpayer compliance. This research employs a qualitative descriptive method with data collection techniques including financial statement documentation, observation, and interviews. The results indicate that the cooperative has fulfilled its tax obligations in terms of tax calculation, payment, and reporting through the e-form system. However, the cooperative has not conducted fiscal reconciliation in determining taxable income. These findings suggest that the implementation of taxation aspects at the Balai Diklat Keagamaan Cooperative in Padang has not yet fully complied with the prevailing tax laws and regulations. Abstrak Pajak merupakan sumber utama penerimaan negara yang berperan penting dalam mendukung pembiayaan pembangunan dan peningkatan kesejahteraan masyarakat. Dalam rangka meningkatkan kepatuhan wajib pajak, pemerintah melakukan modernisasi sistem administrasi perpajakan melalui penerapan e-registration, e-SPT, e-form e-filing, dan e-billing. Penelitian ini bertujuan untuk menganalisis penerapan aspek perpajakan pada Koperasi Balai Diklat Keagamaan Padang sebagai bentuk kepatuhan wajib pajak. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data berupa dokumentasi laporan keuangan, observasi, dan wawancara. Hasil penelitian menunjukkan bahwa koperasi telah melaksanakan kewajiban perpajakan dalam hal perhitungan, pembayaran, dan pelaporan pajak melalui sistem e-form. Namun, koperasi belum melakukan rekonsiliasi fiskal dalam penentuan penghasilan kena pajak. Temuan ini menunjukkan bahwa penerapan aspek perpajakan pada Koperasi Balai Diklat Keagamaan Padang belum sepenuhnya sesuai dengan ketentuan peraturan perundang-undangan perpajakan yang berlaku.